STATUS BADAN HUKUM TERHADAP PERSEROAN TERBATAS YANG DIPUTUS PAILIT - Agustina Ni Made Ayu Darma Pratiwi (Jurnal Hukum Saraswati (JHS), 2019)
Writing entitled "Status of Legal Entity Towards a Broken Company Limited Liability Company" The company has declared bankruptcy in an insolvency state and the revocation of the Company's business license. The liquidation of the Company does not eliminate the status of the Company's legal entity directly, the status of the new legal entity ends with the completion of liquidation and the liability of the liquidator is accepted by the General Meeting of Shareholders or the Court, by declaring bankruptcy, the company cannot carry out its activities and cannot even carry out transactions with other parties except for liquidation. The only activities that can be carried out are liquidation or settlement namely collecting receivables, calculating all company assets and all of them are sold to payoff the company's debts.